School to Work Opportunities Act Policy–An Effort at Backward Mapping - Recesso, Arthur M. (Education Policy Analysis Archives, 1999)
This study examined the intent of federal policy and the actual implementation within local school districts. Specifically, the focus is on the Federal School to Work Opportunities Act of 1994 and its implementation in 47 school districts in upstate New York as part of a consortium during the 1995-96 school year. The purpose of the study was to determine 1) the extent to which an agreement to participate in a consortium arrangement designed to facilitate the implementation of a specific Federal or state policy resulted in the active implementation efforts by individual consortium members, and 2) how a high school setting where School to Work activities were perceived by local stakeholders as having great specific and important effects differed from a high school setting where School to Work activities were perceived by local stakeholders as having some or no effect. A bottom-up backward mapping policy analysis model was used for the purposes of this study. Local level data was used to create performance, environment, technology implementation, and School to Work implementation profiles of local high schools. Regression and correlation analyses were used to determine the relationship between stakeholder perceptions and local high school characteristics. Results of the study were reported and interpreted with the aim of furthering research and knowledge of policy analysis and the use of local level data to determine the success of policy implementation. This study found that variation between federal intent and local adaptation is explained by characteristics of the high school and perceptions of stakeholders. School to Work policy implementation, perceived by the high school administrator as a stakeholder, varied significantly by high school student performance, environment in which the high school operates, and level of technology implementation in the high school. Results indicated that the backward mapping policy analysis model is effective in determining the actual levels of policy implementation. Backward mapping results in a definitive explanation of the role of the local actor and the use of discretion in decision making. The final analysis as a result of backward mapping goes beyond the measurement of policy objectives being met and explains the meaning of local level participation.